2013
DOI: 10.4028/www.scientific.net/amm.357-360.1389
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Compressive Performance of Concrete Exposed to High Temperature Based on Microstructure Analysis

Abstract: Combined with strain gauge measurement method, the modified split Hopkinson pressure bar was adopted to investigate the behavior of normal concrete and steel fiber reinforcement concrete exposed to 400°C and 800°C under axial impact compressive loading. The experimental results show that compared with normal temperature, the compressive strength and elasticity modulus of normal concrete exposed to 400°C and 800°C decrease obviously. The transformation of concrete exposed to high temperature in microstructure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…On the other hand, above 600°C, the CaCO 3 decomposition is detectable using the thermal analysis/ chemical analysis coupling method 11 or thermogravimetric-differential thermal analysis (TG-DTA). 9 Furthermore, above 720°C, the decomposition forms active CaO that can react with SiO 2 to form calcium silicate in accordance with the following reaction: 12,[18][19][20] 2 CaO+SiO 2 ® Ca 2 SiO 4…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, above 600°C, the CaCO 3 decomposition is detectable using the thermal analysis/ chemical analysis coupling method 11 or thermogravimetric-differential thermal analysis (TG-DTA). 9 Furthermore, above 720°C, the decomposition forms active CaO that can react with SiO 2 to form calcium silicate in accordance with the following reaction: 12,[18][19][20] 2 CaO+SiO 2 ® Ca 2 SiO 4…”
Section: Resultsmentioning
confidence: 99%
“…3 The effect of a high-temperature exposure on concrete has been wildly researched. [4][5][6][7][8][9] It was demonstrated that when exposed to high temperatures, water evaporation, disintegration of hydration products and aggregates, coarsening of the microstructure and an increase in the porosity can be observed in concrete. 4,5 Most of all, with the increasing temperature, the strength and elastic modulus of concrete became lower and lower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since impact loads and the heating occur more frequently in structures, dynamic mechanical properties of engineering materials have been investigated (Yin et al 2015(Yin et al , 2018a(Yin et al , 2018bLi et al 2016;Fu et al 2017), as well as those subjected to the heat treatment (Li et al 2012;Huo et al 2013). For example, Yang et al (2013) discovered that the dynamic compressive strength decreases with the increasing temperature by carried out the dynamic experiment on heat-treated concrete, indicating that dynamic mechanical properties also are obviously influenced by the temperature.…”
Section: Introductionmentioning
confidence: 99%